Peran Guru dalam Meningkatkan Dukungan Sosial bagi Anak Berkebutuhan Khusus di Lingkungan Sekolah Inklusi - Fitriani, Fitriani; Nirmalasari, Susanti; Rahmi, Devi Silvia (Universitas Medan Area, 2024)
This research aims to explore and understand the role of teachers in enhancing social support for children with special needs in the context of inclusive education. This study attempts to provide an overview of how teachers can contribute positively to creating an inclusive learning environment, particularly at TK Harsya Ceria in Banda Aceh City. The research employs a case study design along with qualitative methodology. Field notes, observations, and interviews are the strategies used in this study to gather data. According to the research findings, inclusive education is crucial for children, especially those with special needs. Due to a lack of resources, including staff members with knowledge of special needs, not all-inclusive schools can accommodate students with special needs. Teachers play a vital role in inclusive education, and some roles of teachers that can enhance social support for children with special needs in inclusive education include 1) Regular communication with the families of children with special needs; 2) Explaining the benefits and objectives of an inclusive learning-friendly environment to parents of students with special needs; 3) Preparing children to socially interact with the community as part of the curriculum; 4) Involving parents in the classroom with regular meetings; and 5) Collaborating with parents as educators to help them understand the concept of inclusion.